Effects of extracellular polymeric substances on granulation of anoxic sludge in sequencing batch reactor - Wang, Binbin (Water science and technology : a journal of the International Association on Water Pollution Research, 2012)
Variations of extracellular polymeric substances (EPS) and its components with sludge granulation were examined in a lab-scale sequencing batch reactor (SBR) which was fed with sodium nitrate and sodium acetate. Ultrasonication plus cation exchange resin (CER) were used as the EPS extraction method. Results showed that after approximately 90 d cultivation, the sludge in the reactor was almost granulated. The content of extracellular polysaccharides increased from 10.36 mg/g-VSS (volatile suspended solids) at start-up with flocculent sludge to 23.18 mg/g-VSS at 91 d with matured granular sludge, while the content of extracellular proteins were almost unchanged. Polysaccharides were the major components of EPS in anoxic granular sludge, accounting for about 70.6-79.0%, while proteins and DNA accounted for about 16.5-18.9% and 4.6-9.9%, respectively. It is proposed that EPS play a positive role in anoxic sludge granulation and polysaccharides might be strongly involved in aggregation of flocs into granules